So the answer is :

3(sinx / cosx) + 2cosx = 0

3sinx + 2cosx / cosx = 0

But then the next line just goes to

3sinx + 2cosx = 0

How can you divide it by cosx and not change the top? I'm so confused!

And then I don't know where I would go from here?

- Thread starter smurfledurple
- Start date

Similar Math Discussions | Math Forum | Date |
---|---|---|

Integrate sinx - 2cosx | Calculus | |

Solve sinxy + xycosxy + x^2cosxy(dy/dx)=0 | Differential Equations |

Similar threads |
---|

Integrate sinx - 2cosx |

Solve sinxy + xycosxy + x^2cosxy(dy/dx)=0 |